A Statewide Strategy for Expanding Graduate Medical Education by Establishing New Teaching Hospitals and Residency Programs. (September 2015) - Nuss, Michelle A.; Robinson, Ben; Buckley, Peter F.
<x xml:space="preserve">Abstract</x> The graduate medical education (GME) system in the United States is in need of reform to ensure that the physician workforce being trained is able to meet the current and future health care needs of the population. However, GME funding to existing teaching hospitals and programs relies heavily on support from Medicare, which was capped in 1997. Thus, new, innovative models to expand GME are needed. To address physician shortages, especially in primary care and general surgery and in rural areas, the state of Georgia implemented a statewide initiative. They increased medical school enrollment by 600 students from 2000 to 2010 and committed to establishing new GME programs at new teaching hospitals to train 400 additional residents by 2018. As increasing the capacity of GME programs likely increases the number of physicians practicing in the state, these efforts aim to encourage trainees to practice in Georgia. Although new teaching hospitals, like these, are eligible for new Medicare funding, this approach to expanding GME also incorporates state funding to cover the start-up costs associated with establishing a new teaching hospital and GME program. In this article, the authors provide background on the current state of GME funding in the United States and on the physician workforce and medical education system in Georgia. They then outline the steps taken to expand GME by establishing new teaching hospitals and programs. They conclude by sharing outcomes to date as well as challenges faced and lessons learned so that others can follow this novel model.